Temporal trends in obstetric anal sphincter injury from the first vaginal delivery in Austria, Canada, Norway, and Sweden. (25th August 2021) - Gyhagen, Maria; Ellström Engh, Marie; Husslein, Heinrich; Koelbl, Heinz; Nilsson, Ida E. K.; Schulz, Jane; Wagg, Adrian; Milsom, Ian
Abstract: Introduction: Obstetric anal sphincter injuries (OASI) are severe complications that can cause considerable short‐ and long‐term morbidity. Austria, Canada, Norway, and Sweden have similar socio‐economic characteristics, and all four countries have access to national birth registers. In this study, we hypothesized that the incidence of OASI should be very similar for different obstetric scenarios in these four countries. Therefore, the aim was to compare the incidence of OASI in these four countries in primiparous women, with spontaneous or instrumental delivery (vacuum or forceps), and in women with a first vaginal birth after cesarean section (VBAC). Material and methods: Aggregated data on 1 933 930 vaginally delivered primiparous women and women with VBAC were retrieved from the birth registers gathered in Austria, Canada, Norway, and Sweden. The annual rate of OASI (ICD‐10 codes O70.2–O70.3) was presented as the percentage of women with a spontaneous delivery, vacuum or forceps delivery, and a VBAC during the period 2004–2016. Results: The incidence of OASI varied considerably between countries and over time. Canada and Sweden had the highest rates, and Austria and Norway the lowest. In Norway, the rate of OASI decreased consistently for all types of deliveries after introducing a perineal protection program in 2004 ( p  < 0.001). During vacuum delivery, the incidence of OASI varied between countries from 4.1% to 15.5% across the study period. In Canada and Norway, the rate of OASI after a forceps delivery was similar in 2004 at ~20% and with differing trajectories to 24.3% (β 0.49) and 6.2% (β −1.15) (trend, all p  < 0.001) in 2016. Conclusions: This comparative register study suggests that there may be considerable potential for lowering the incidence of OASI. The perineal protection program implemented by Norway has been successful. Each country should critically, without prejudice, analyze their current clinical practices and rate of OASI and consider the best preventive strategy.